LONG-TERM RESULTS OF COMBINED X-RAY ENDOVASCULAR SURGICAL TREATMENT OF PATIENTS WITH DUCTAL ADENOCARCINOMA OF THE PANCREATIC HEAD - A. A. Polikarpov; A. V. Pavlovsky; A. S. Gulo; A. S. Popov; P. G. Tarazov; D. A. Granov (Вестник хирургии имени И.И. Грекова)
On the basis of the results of treatment of 105 patients with locally advanced ductal adenocarcinoma of the pancreatic head the authors present the results of work over a period of time since 1999 to 2009. In the main group the combined treatment was used for 51 patients: the non-adjuvant selective chemoembolization of the pancreatic head adenocarcinoma was performed, than standard gastropancreatoduodenal resection with lymphodesection and 6 cycles of adjuvant chemoinfusion in celiac trunk were completed. In control group standard gastropancreatoduodenal resection was performed. In the group of combined treatment the 1-, 2-, 3-year survival rates consist of 80.4%, 58.8% and 43.1%, respectively. The average life span was 22.3±2.1 months. The average life span of 54 patient of control group was 8.4±2.1 months and a common 3-year survival consists of 13%. There was no lethality after the performance of X-ray endovascular procedures and gastropancreatoduodenal resection. Postoperative complications reliably didn’t differ in both groups.